Inhalation by design: Dual pharmacology β-2 agonists/M3 antagonists for the treatment of COPD - Jones, Lyn H.; Baldock, Helen; Bunnage, Mark E.; Burrows, Jane; Clarke, Nick; Coghlan, Michele; Entwistle, David; Fairman, David; Feeder, Neil; Fulton, Craig; Hilton, Laura; James, Kim; et al. (Bioorganic & medicinal chemistry letters, 2011)
This paper describes the successful design and development of dual pharmacology β-2 agonists-M3 antagonists, for the treatment of chronic obstructive pulmonary disorder using the principles of ‘inhalation by design’. A key feature of this work is the combination of balanced potency and pharmacodynamic duration with desirable pharmacokinetic and material properties, whilst keeping synthetic complexity to a minimum.